2017
DOI: 10.1089/thy.2016.0345
|View full text |Cite
|
Sign up to set email alerts
|

TSHRGene Polymorphisms in the Enhancer Regions Are Most Strongly Associated with the Development of Graves’ Disease, Especially Intractable Disease, and of Hashimoto's Disease

Abstract: Among the evaluated TSHR gene SNPs, the rs4411444 GG genotype and the rs4903961 C allele in the enhancer regions of the TSHR gene were most strongly associated with the development of GD, especially intractable disease, and that of HD, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…In 2011, Mihaela Stefan et al revealed a new mechanism of interaction between the TG promoter SNP variant with viral infection to AITDs, which laid the foundation for further exploration [32]. However, an explicit link [33][34][35][36][37]. But which SNPs of TSHR can confer risk for AITDs remains an intractable problem.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Mihaela Stefan et al revealed a new mechanism of interaction between the TG promoter SNP variant with viral infection to AITDs, which laid the foundation for further exploration [32]. However, an explicit link [33][34][35][36][37]. But which SNPs of TSHR can confer risk for AITDs remains an intractable problem.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate gene case-control studies identified several putative susceptibility variants associated with AITD development or progression. These included variants in genes encoding proteins related to inflammation, modulation of immune responses, or specific for the thyroid, such as: human leukocyte antigen (HLA) class I and class II, forkhead box P3 (FOXP3), cytotoxic T-lymphocyte-associated protein 4 (CTLA4), cluster of differentiation 40 (CD40), protein tyrosine phosphatase, non-receptor type 22 (PTPN22), selenoprotein S (SEPS1), IL4, IL2 receptor α (IL2RA), VDR, Tg, TSH receptor (TSHR), signal transducer and activator of transcription 3 (STAT3), and STAT4, with HLA-DR3 carrying the highest risk ( 2 , 114 120 ). Among non-HLA genes, CTLA4 and PTPN22 were most consistently identified as predisposing to both HT and GD ( 121 124 ), while the TSHR locus appears to be specific for GD, but not HT, suggesting some genetic differences between these two types of AITD ( 125 , 126 ); however, similar to PCOS, candidate gene screening for HT susceptibility mainly generated controversial and non-replicable findings ( 127 132 ).…”
Section: Autoimmune Thyroid Diseasementioning
confidence: 99%
“…In the past two decades, genetic studies in AITD have developed from candidate gene analyses, whole-genome linkage screening, genome-wide association study (GWAS), whole-genome sequencing, and epigenetic studies (16, 4042). Some thyroid-specific genetic factors are found to be associated with AITD, such as polymorphisms in TSHR gene and thyroglobulin (TG) gene (4345). Emerging evidence has suggested the important role of immunogenetics in the pathogenesis of AITD, and polymorphisms in these immune-modulating genes can impair immune tolerance and alter T cells’ interactions with antigen-presenting cells during the development of AITD (16, 46).…”
Section: Introductionmentioning
confidence: 99%